Holy cows and spilt milk: The impact of religious conflict on firm-level productivity - Jeanet Sinding Bentzen; Nina Boberg-Fazlić; Paul Sharp; Christian Volmar Skovsgaard; Christian Vedel (European Historical Economics Society (EHES), 2023)
We consider the impact of non-violent religious conflict on firm-level productivity. We zoom in on a Protestant and otherwise very homogeneous country: early twentieth century Denmark. We exploit variation due to the emergence of pietist movements who fought for the hearts and minds of Danes. In the countryside, much of the religious debate concerned whether or not creameries - the main catalyst of the industrial revolution in Denmark - should be closed on Sundays in accordance with the Third Commandment. We construct a rich microlevel dataset for 964 creameries and combine this with various measures of the intensity of the religious conflict. Exploiting variation in preaching by a prominent religious figure, we provide plausibly causal evidence that religious conflict hampered firm-level productivity. Examining the mechanism, we proceed to demonstrate that the reduction in productivity is due to the religious conflict rather than whether or not the factory produced on Sundays.
Keywords: N33; N34; O12; O13; Z12; 330; Dairying; Denmark; productivity; religiosity